Community Participation in Hygiene and Environmental Maintenance of Candinegoro Tourism Village in the Middle of the Covid-19 Pandemic: Partisipasi Masyarakat dalam Kebersihan dan Pemeliharaan Lingkungan Hidup Desa Wisata Candinegoro di Tengah Pandemi Covid-19 - Nabelliasari , Iffany; Supardi; Valentina , Happy; khotimah, Nurul Khusnul; Andrian, Moch. Fani; Alwi, M.Hafis (Procedia of Social Sciences and Humanities, 2022)
Cleanliness iis ia isign igood ihygienie. iHumans ineed ito imaintain ia iclean ienvironment iand ipersonal ihygiene ito ibe ihealty, inot ismelly, inot ispreading idirt, ior itransmitting igerms ito ithemselves. iThe iactive irole iof ihumans ifor itheir ienvironment iis irelated ito ithe iculture ithat iis iowned iby ihumans ithemselves. iHuman ibehavior itowards ithe ienvironment ican ibe iknown iby ithe iawareness iof ithe iimportance iof ithe ienvironment ifor ithe ilife iof ieach iindividual. iCoronavirus iia ia izoonotic ior ivirus ithat iis itransmitted ibetween ianimals iand ihumans. iThe ispread iof ithis idisease ihas ihad ia iwide isocial iand ieconomic iimpact. iCovid-19 idisease ican iinfect iwithout igiving iclinical isymptoms, iso isufferers ido inot ifeel iany ichanges iin ithemselves. iSome iof ithe isymptoms ifelt iranging ifrom ithe icommon icold, icough iand irunny inose. iMore isevere iclinical isymptoms isuch ias ifever, isore ithroat, imuscle iaches, iloss iof ismell iand itaste, ishortness iof ibreath iand ieven ideath. iThe ipurpose iof ithis istudy iwas ito ifind iout ihow ithe iparticipation iof ithe iCandinegoro iTourism iVillage icommunity iin imaintaining ienvironmental icleanliness iduring ithe iCovid-19 ipandemic. iIn ithis iactivity, ithe ivillage iofficials iinvited iPKK iwomen iand iMuhammadiyah iSidoarjo iUniversity istudents ito ihelp ithe icommunity iin imaking ienvironmental iimprovements. iPartnership icooperation iis ian iappropriate imethod ito iestablish icooperation iwith ithe iCandinegoro iTourism iVillage icommunity. i